Aquaculture : - Bardach, John E. (Wiley-Interscience, 1972)
The book details: chemical processes controlling carbonate stability in seawater; the effect of captivity on physiological processes; sensory processes of fishes, including vision, hearing, and electroreception; diseases of seawater fishes and treatment methods.